New Testament Considerations on Unity and "Amicable Separation" in the United Methodist Church - Bounds, Christopher T. (The Asbury journal, 2014)
This paper explores the proposal of "Amicable Separation" in The United Methodist Church through the lens of New Testament teaching on Church unity and schism. First, the concept of ecclesial oneness is examined closely in the Gospel of John, Ephesians, and other related passages. Second, every instance of schism or threat of schism is studied in Acts, I Corinthians, Galatians, Colossians, I Timothy, and I and II John to see how separation is understood and addressed. After a summary of the study is given, application is made finally to the "Amicable Separation" proposal.